Expectation violation reduces the accessibility of implicit suicidal concepts and explicit life concepts - Liu, Bo; Wu, Yuntena; Jin, Tonglin; Lei, Zeyu (Frontiers in Psychology, 2025)
IntroductionTerror Management Theory posits that threats to cultural worldviews increase death concept accessibility. Suicide and death concepts are related and jointly represent the fear of life. Threats to cultural worldviews may similarly increase suicide concept accessibility. This study situates worldview threats within the broader context of expectation violation and investigates its impact on both implicit and explicit suicide concept accessibility.MethodsFour experiments were conducted to examine this relationship. Expectancy violation was induced by violating the stated purpose of an intelligence test, challenging established beliefs about evolution, and presenting logically incoherent sentences. Implicit concept accessibility was assessed using a lexical decision task requiring discrimination between words and non-words. In contrast, explicit concept accessibility was measured through a semantic categorization task involving direct judgments of word meaning.ResultsThe results showed that expectation violation, compared to expectation confirmation, reduced implicit suicide concept accessibility (Experiments 1 and 2) and explicit life concept accessibility (Experiments 3 and 4).DiscussionThe impact of expectation violation on suicide concept accessibility may reflect the underlying cognitive framework of increased suicide risk, highlighting the importance of targeting expectancy violation incidents in clinical suicide intervention.